PSYCHOLOGY OF CONSUMER CHOICE AND ITS INFLUENCE ON PRICING IN MARKET CONDITIONS - I. L. Goncharov; O. A. Gorelova (Вестник университета)
The schemes of the decision-making process of an individual when consuming various goods and services using the components of economic psychology have been considered. Relevant from the point of view of economic psychology characteristics of buyer behavior that have a direct impact on his attitude to the price level of a product or service and on his reaction when the price changes for them have been presented and reviewed. The used “models” of consumer behavior of motivation, explaining not only the purchase by him of this product, but also his decision to have this product have been shown. Building models of purchase motivation allows manufacturers not only to explain consumer behavior, but also to influence it. Knowing all these nuances and skilful use of them, manufacturers have the opportunity significantly facilitate the pricing process for their goods and make a more accurate calculation of the “fair” price, which will not alienate the consumer. Two global approaches to segmentation of the consumer market have been considered, the use of which allows the manufacturer to assess the company’s competitiveness, assess the market size, and assess the customer’s commitment.